2003
DOI: 10.1038/sj.bjc.6601406
|View full text |Cite
|
Sign up to set email alerts
|

Applications of array technology: identification of molecular targets in bladder cancer

Abstract: High-throughput microarrays are being used in expression profiling analyses with the objecties of gene and pathway discovery, functional characterization of genes, and tumor subclassification. This review summarizes bladder cancer studies dealing with both in vitro models and clinical specimens, using distinct microarray platforms for target discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Although gene expression has been extensively profiled in bladder tumor tissue samples, little is known about its correlation with gene expression profiles of urine samples. To this end, using microarrays, we identified a high number of differentially expressed genes between UCC and control samples as well as between low-grade (LG) and high-grade (HG) bladder tumors, in accordance with many other studies (6,7,13,14). But more interestingly, we showed that these differentially expressed genes could also be identified in urine samples by real-time quantitative reversetranscription PCR (qRT-PCR; ref.…”
supporting
confidence: 56%
“…Although gene expression has been extensively profiled in bladder tumor tissue samples, little is known about its correlation with gene expression profiles of urine samples. To this end, using microarrays, we identified a high number of differentially expressed genes between UCC and control samples as well as between low-grade (LG) and high-grade (HG) bladder tumors, in accordance with many other studies (6,7,13,14). But more interestingly, we showed that these differentially expressed genes could also be identified in urine samples by real-time quantitative reversetranscription PCR (qRT-PCR; ref.…”
supporting
confidence: 56%
“…At the present time, there is no single molecular marker that provides 100% accuracy in predicting tumor behavior (43,45,49), and as a result molecular prognostication is moving toward a multiplex-marker setting. This is particularly true for microarray-based approaches that use multi-gene molecular classifiers (50,51). Several studies have applied genomic microarray technology to gain insight into the changes in expression profiles that occur during different stages of bladder cancer progression, generating disease classifiers and outcome predictors by using several key genes to built a multi-marker molecular signature that is significantly associated with pathological stage, tumor grade, and overall survival (52)(53)(54).…”
Section: The Transcriptional Regulator Ppar␥ Is Not Responsible For Lmentioning
confidence: 99%
“…In particular, the cancer epigenome alterations better characterized in bladder cancer include global changes in DNA methylation, altered histone modification, and miRNAs patterns [7,[31][32][33][34][35][36][37][38][39][40]. Because epigenetic features such as global DNA hypomethylation and promoter-specific hypermethylation can be commonly observed in benign neoplasias and early-stage tumors, it is becoming apparent that epigenetic deregulation may precede preliminary transforming events such as mutations in tumor suppressors, protooncogenes, or both, and genomic instability [6].…”
Section: Epigenetic Factors Contribute To Bladder Cancer Tumorigenesimentioning
confidence: 98%
“…In fact, these "epimutations" sometimes provide the second hit for cancer initiation postulated by the two-hit model, as they can silence the remaining active allele of previously mutated tumor suppressors [1]. A few studies have explored the link between the methylation patterns observed in bladder cancer with the expression of these proteins [28,29], as compared to studies assessing candidate-driven hypermethylation [30][31][32][33][34][35][36][37][38][39][40]. The disturbance of the DNA methylation landscape in transformed cells has been recently supported by the finding of somatic mutations in DNMT3A in acute myeloid leukemia [41].…”
Section: Hypermethylation: a Relevant Epigenetic Modifications In Cancermentioning
confidence: 98%
See 1 more Smart Citation